If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5m = 6m + -1 Reorder the terms: -5m = -1 + 6m Solving -5m = -1 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -5m + -6m = -1 + 6m + -6m Combine like terms: -5m + -6m = -11m -11m = -1 + 6m + -6m Combine like terms: 6m + -6m = 0 -11m = -1 + 0 -11m = -1 Divide each side by '-11'. m = 0.09090909091 Simplifying m = 0.09090909091
| 0=4m^2-20m | | -6x=-9.1 | | -1/4=-2/3u-1/5 | | 0=p^2-5p | | 0=y^2-10y+9 | | y=-(8)+3 | | 8+y-14=2 | | y=-(3)+3 | | 294=6s^2 | | 9a-a-5a= | | 9/x-1(7/x-3) | | (x)1.5+(y)0.5=18 | | 1/2+(t+7)=32 | | -5(3)(-5)(4)= | | (4-w)(2w+5)=0 | | 3x-(6)=30 | | 4x-3+6x+23=180 | | (4u-7)(8-u)=0 | | 30x+50y+70z=600 | | y=9/2x+5 | | 2x+3+25=45 | | 3(-4)-6/-4=12 | | 3j+(4/3)=3j | | -(-5v+y)-(-6y+v)= | | (-10y^2-14)-(-5y^2+7)=0 | | -5a^6-(-7a^6-14)=0 | | -3-(-g)=-8 | | w^2=4w+3 | | 3/7w-11=-4/7 | | 8x^9-(6x^9-7)=0 | | 5z^6-(-3z^6-3v)=0 | | 10x-185=4x-11 |